PENGARUH MINYAK DAUN CENGKEH (SYZYGIUM AROMATICUM L) TERHADAP SITOPHILUS ORYZAE L (COLEOPTERA: CURCULIONIDAE) (THE EFFECT OF CLOVE LEAF OIL (SYZYGIUM AROMATICUM L.) TO SITOPHILUS ORYZAE) - PENGARUH MINYAK DAUN CENGKEH (SYZYGIUM AROMATICUM L) TERHADAP SITOPHILUS ORYZAE L (COLEOP, A.A.A. (AGRITROP, 2010)
The use of synthetic pesticides are generally less secure because it can be detrimental to human health and the environment, therefore, sought a safe control for the products, people and the environment. Alternatives that need to be developed is the product of the biological nature of the organism narrow spectrum target. This research aims to determine the effect of clove leaf oil to S. oryzae. Research using complete random design (CRD) with various concentrations of clove leaf oil formulation of 0.50%; 0.38%; 0.25%; 0.13 and control, with 5 times replications. The influence of clove leaf oil can be determined by the contact test, repelensi resources, the development of insect populations. The results showed that the leaf oil of clove with a concentration of 0.50%; 0.38%; 0.25% and; 0.13 have influence as a contact poison, not as a repelen but tends to antraktan S. oryzae, as well as inhibiting the development of the insect S. oryzae